Identity in elite level disability sport: a systematic review and meta-study of qualitative research - Crossen, W.; Wadsworth, N.; Ronkainen, N.; Haslett, D.; Tod, D. (International Review of Sport and Exercise Psychology, 2025)
This meta-study evaluated qualitative identity literature within elite disabled sport. Following a systematic search of EBSCO SPORTDiscus, MEDLINE, PsycINFO, and Web of Science, nine articles met the inclusion criteria. The meta-study examined how identity was framed from participant or author perspectives, employing narrative analysis to understand the participant stories and broader storylines crafted by authors. Two distinct narratives were co-constructed; Re-birth: characterising athlete identity experiences and how overcoming career challenges developed traits necessary for elite athlete status, and Tragedy: how authors` interpretations indicated that although athletes achieved personal sporting success, the `bigger battle` of how disability was presented within society remained. The Re-birth and Tragedy narratives update the prospective gap between how elite disability athletes story their experiences and their framing within society.